The Future of Human Resources - Trends, Reflections and Strategies. - Folarin, Kehinde (European Journal of Human Resource, 2021)
The future of human resource management will be effected by several factors. The basic tasks of a human resource manager have and will remain the same, but the way these tasks are conducted will change. The two key factors which have been the main focus of this research paper are globalization and technological development. Globalization and technological development are stimulating each other and are both necessary for continuous development and economic growth in the world of business. This paper will be looking at the effects of these two factors with regards of human resource management and how it will affect the future. This paper concludes that; to remain competitive in the industry, organizations need to address their HR issues by ensuring the employee's needs are met and streamlining transactions. Reshaping the future of the HR requires organizations to manage change. The HR will provide the business with the needed insights that are actionable and data-driven to enable better decision-making that will drive business to success.